EVALUASI AGRIBISNIS STROBERI ORGANIK DI KABUPATEN BOLAANG MONGONDOW TIMUR PROVINSI SULAWESI UTARA - Agnes Estephina Loho; Jen ., Tatuh; Gene H. M. Kapantow (AGRI-SOSIOEKONOMI, 2018)
The purpose of this study was to evaluate organic strawberry agribusiness in the East Bolaang Mongondow Regency by evaluating the dimensions of agribusiness players, the dimensions of agribusiness activity and the dimensions of behavior of organic strawberry agribusiness. The method used in this study was the survey method. The selection of the location of the study was done intentionally by determining the highland area in the East Bolaang Regency that cultivated strawberries. The area was the village of Mooat, Guaan Village, and New Bongkudai Village. This research begins in May to August 2018. The types of data used in this study were primary and secondary data. Data were analyzed using income analysis, added value, and were evaluated with an evaluation structure design adopted from the modified Hammond Evaluation Structure into agribusiness. The results of the study showed that agribusiness players consisting of key players had not made strawberries as commercial commodities while the tourism business of D’Mooat had made strawberries as a commercial commodity. The agricultural input activities were in the form of the use of the workforce of the community around the tourist area and the provision of production facilities, both purchased and made by themselves. The agricultural production activities had not fully utilized organic materials with an average production of 1,080 kg / year and the revenues of Rp.128,505,250/year for the area of 2,000 m2. The agricultural industry activities provided added value around of Rp. 57,000 / kg for strawberries and the average profit of Rp. 52,870 / kg through processing strawberries into strawberry juice, smoothie strawberry juice and dragon berry juice. Agricultural marketing activities were take place only in the tourist attractions area. The agricultural service activities were in the form of credit from Bank (BRI) while coordination with related agencies has not been established. The production technique behavior was good; the agribusiness management behavior was still in traditional way, whereas the agribusiness system behavior have not yet.